2000
DOI: 10.1086/315339
|View full text |Cite
|
Sign up to set email alerts
|

Natural History of Human Immunodeficiency Virus Type 1 Viremia after Seroconversion and Proximal to AIDS in a Large Cohort of Homosexual Men

Abstract: The natural history of human immunodeficiency virus type 1 (HIV-1) viremia and its association with clinical outcomes after seroconversion was characterized in a cohort of homosexual men. HIV-1 RNA was measured by reverse-transcription polymerase chain reaction (RT-PCR) in stored longitudinal plasma samples from 269 seroconverters. Subjects were generally antiretroviral drug naive for the first 3 years after seroconversion. The decline in CD4 lymphocyte counts was strongly associated with initial HIV RNA measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
222
0
6

Year Published

2002
2002
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 310 publications
(248 citation statements)
references
References 25 publications
20
222
0
6
Order By: Relevance
“…Studies suggest so far that the level of CD4 counts prior to HIV infection does not influence prognosis for those who get infected. Males from the Multicenter AIDS Cohort Study (MACS) with high CD4 counts prior to HIV infection had, compared to others, higher viral load, and steeper slope of CD4 counts decline in the early months following infection, so that there was no evidence for a beneficial effect of higher CD4 counts before infection (31). Also, it has been shown that females have higher CD4 counts than males at the time of HIV seroconversion, AIDS development, and death, without difference in survival compared to males (32).…”
Section: Discussionmentioning
confidence: 99%
“…Studies suggest so far that the level of CD4 counts prior to HIV infection does not influence prognosis for those who get infected. Males from the Multicenter AIDS Cohort Study (MACS) with high CD4 counts prior to HIV infection had, compared to others, higher viral load, and steeper slope of CD4 counts decline in the early months following infection, so that there was no evidence for a beneficial effect of higher CD4 counts before infection (31). Also, it has been shown that females have higher CD4 counts than males at the time of HIV seroconversion, AIDS development, and death, without difference in survival compared to males (32).…”
Section: Discussionmentioning
confidence: 99%
“…This is surprising since the immunologic and virologic events that occur during the earliest stages of infection can have a strong impact on subsequent disease progression. [30][31][32] We therefore assessed the effects of T-cell activation and plasma HIV RNA levels on CD4 ϩ T-cell changes over time in a prospective cohort of acutely and recently HIV-infected adults. Our primary objective was to determine the relative contributions of viremia and T-cell activation to the rate of CD4 ϩ T-cell loss.…”
Section: Introductionmentioning
confidence: 99%
“…This understanding is solidly underpinned by two long-standing observations. First, patients with higher viral loads progress to disease more quickly (2,3). Second, the possession of certain human leukocyte antigen (HLA) class I molecules (e.g., HLA B35) predisposes patients to rapid disease progression, whereas others (e.g., HLA B27 and HLA B58) endow them with a longer asymptomatic period (4)(5)(6)(7)(8)(9).…”
mentioning
confidence: 99%